Changing Patterns in Lifestyle, Food Intake and Health Status between Selected Beneficiary People and Non-beneficiary People of Urban Slum in Dhaka City - Islam, MS; Kurshed, AAM; Azad, TMA; Bhuyan, MAH (Bangladesh Journal of Nutrition, 2013)
To see the improvement in lifestyle, food intake and nutritional status of Beneficiary people of Shiree Project under Dushtha Shasthya Kendra, a comparative cross sectional study was done in Kamrangirchar slum among extreme poor people of Dhaka city and compared with nonbeneficiary households. Beneficiary households of MDG-1 under Shiree Project got household economic intervention packages. In this stuy it is found that mean monthly income of the family was 6175.65 Tk in beneficiary group and 4288.14 Tk in non-beneficiary group. The mean monthly expenditure on food items of family was 3787.83 Tk in beneficiary group and 2796.61 Tk in non-beneficiary group. About 34 percent beneficiary households and 75 percent of all non-beneficiary households were poor having households monthly income less than 3000 taka. Some 15.7 percent beneficiary households had five amenities out of selected six and only 1.7 percent non-beneficiary households had five amenities. So, socio-economic condition of beneficiary extreme poor people has improved. Consumption of food items was significantly more in beneficiary households than non-beneficiary ones. Some 74 percent beneficiary households consumed four or more food items daily and 26 percent non-beneficiary households consumed four or more food items daily. On average 3.37 food items were consumed by beneficiary households and 2.49 food items by non-beneficiary households daily. More than 60% of the beneficiary people ate full stomach meals and less than 25 % of non-beneficiary people could afford to eat the same. So, beneficiary people were more food secure and more food diversified than non-beneficiary people. Nutritional status of the children by MUAC, Weight for Age Z-score, and Height for Age Z-score showed no significant difference between beneficiary and non-beneficiary group. Prevalence rate of underweight (Weight for Age Z-score) was 60.5% in beneficiary children and 65.9% in non-beneficiary children. Significant difference (P=0.044) was found by Weight for Height Z-score in both beneficiary and non-beneficiary group. The difference of mothers nutritional status by BMI between beneficiary group and non-beneficiary group was not statistically significant, though percentage of CED was lower and overweight was higher in beneficiary mothers than non-beneficiary ones. Though socio-economic status, food security and food intake were better in beneficiary people than non-beneficiary ones, the outcome of these factors were not significant in clinical and anthropometric status. Beneficiary households were on the way to meet first target of MGD-1 which is related to poverty reduction. But they were far away from reaching the second target and halving prevalence of underweight as described in MDG-1. DOI: http://dx.doi.org/10.3329/bjnut.v24i0.14033 Bangladesh J. Nutr. Vol. 24-25 Dec 2011-2012 pp.15-22